1972
DOI: 10.1172/jci107142
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Mast Cell in the Pulmonary Pressor Response to Hypoxia

Abstract: A B S T R A C T This study investigated the role of the mast cell in the pulmonary arterial pressor response to hypoxia. We found that pulmonary arteries 50-500 iA in diameter have a predictable distribution of perivascular mast cells; that such pulmonary mast cells are degranulated in vivo during alveolar hypoxia; that hypoxia releases histamine from mast cells isolated from the peritoneal cavity without apparent injury to the cells; and that histamine is released from the lung of intact guinea pigs during al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
2

Year Published

1974
1974
1988
1988

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(39 citation statements)
references
References 20 publications
1
36
2
Order By: Relevance
“…Kay and Grover (1975) showed that disodium cromoglycate inhibited the pulmonary pressor response to acute hypoxia in three out of eight anaesthetized dogs, though Howard et al (1975) DEGRANULATION EXPERIMENTS There was no significant difference between the degree of degranulation, either between the hypoxic and control animals or between the three experiments. The reason for the discrepancy between these results and Haas and Bergofsky's (1972) demonstration of hypoxic mast cell degranulation is not clear. Haas and Bergofsky only measured degranulation in perivascular mast cells though this is unlikely to be the explanation as in experiment ii (Table III) the degree of degranulation in the perivascular mast cells and in the lung as a whole was similar.…”
Section: Population and Distribution Of Mast Cells Incontrasting
confidence: 59%
“…Kay and Grover (1975) showed that disodium cromoglycate inhibited the pulmonary pressor response to acute hypoxia in three out of eight anaesthetized dogs, though Howard et al (1975) DEGRANULATION EXPERIMENTS There was no significant difference between the degree of degranulation, either between the hypoxic and control animals or between the three experiments. The reason for the discrepancy between these results and Haas and Bergofsky's (1972) demonstration of hypoxic mast cell degranulation is not clear. Haas and Bergofsky only measured degranulation in perivascular mast cells though this is unlikely to be the explanation as in experiment ii (Table III) the degree of degranulation in the perivascular mast cells and in the lung as a whole was similar.…”
Section: Population and Distribution Of Mast Cells Incontrasting
confidence: 59%
“…Thus, in the dependent regions of the lung, the relative changes in resistance are less. Haas and Bergofsky (1972) have implicated mast cells in the hypoxic response of the lung by demonstrating that these are degranulated and that histamine release is increased in the hypoxic rat and guinea-pig. This work supported the earlier work of Hauge (1968), who used pharmacological agents to block or potentiate the effects of histamine during hypoxia to demonstrate a role for this agent, and suggested that histamine was involved in the hypoxic vasoconstrictor response.…”
Section: Discussionmentioning
confidence: 99%
“…(Pediatr Res 23: 513-518,1988) HPV, hypoxic pulmonary vasoconstriction CS, cromolyn sodium Other studies have refuted the importance of mast cells in the pulmonary pressor response to hypoxia in cats (5), mast celldeficient mice (6), and rats (7). Despite these interspecies differences, a contributing role for mast cells in HPV remains an attractive hypothesis because of the strategic perivascular location of these calls in the lung (3,4,8), and the variety of vasoactive mediators contained within them (9).CS is a known inhibitor of mast cell degranulation and when administered intravenously, has been shown to inhibit or modify HPV in adult sheep (4), dogs (10, 1 I), and newborn lambs (12). Administration of CS by aerosolization directly into the airways would provide an alternative route of delivery and might offer a more efficient means of locally depositing the drug.…”
mentioning
confidence: 99%
“…(Pediatr Res 23: 513-518,1988) HPV, hypoxic pulmonary vasoconstriction CS, cromolyn sodium Other studies have refuted the importance of mast cells in the pulmonary pressor response to hypoxia in cats (5), mast celldeficient mice (6), and rats (7). Despite these interspecies differences, a contributing role for mast cells in HPV remains an attractive hypothesis because of the strategic perivascular location of these calls in the lung (3,4,8), and the variety of vasoactive mediators contained within them (9).…”
mentioning
confidence: 99%